Demographic changes: considerations related to the growth of the elderly population in the Amazonas state mesoregions (Research, Society and Development, 2020)
This paper considers considerations related to the population growth of the elderly in the mesoregions of the state of Amazonas based on information from the Demographic Census of the Brazilian Institute of Geography and Statistics (IBGE). The highlight of the aging population is a worldwide trend that is accentuated in all countries and Brazil is no different. Amazonas has 62 municipalities, grouped into four mesoregions: Norte Amazonense, Sudoeste Amazonense, Centro Amazonense and Sul Amazonense. Thus, the elderly population growth was intense in the Censuses observed, similar to what occurs worldwide, with exponential increase in all mesoregions, relatively distributed in the three others and strongly concentrated in the mesoregion Centro Amazonense, to that which concentrates 50% of the municipalities of the state as well as where the capital Manaus is located.